Perancangan Boost Konverter Pada Sistem Microgrid Bersumber Solar Sel - Ismail, Ihsan; Zakri, Azriyenni Azhari (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Solar cells as one of the new renewable energy sources have an important role in terms of meeting the needs of energy. For this reason, solar cells are employed as an alternative source of electricity generation, both in an off-grid or on-grid state. In this papers presents a step-by-step simulation of a three-phase circuit connected to a network with a solar cell source. The capacity of the solar cell to be simulated is 100 kWp. In this study, solar cells as an alternative generator that will generate three-phase AC loads. This requires a DC-DC boost converter to increase the output voltage of the solar cell and keep the voltage stable during the generation process by tracking the maximum power point using MPPT to extract the maximum power obtained from solar irradiation and channel it to the network. In systems based on solar cells, the inverter is a very critical component for controlling the flow of electricity by converting DC voltage to AC voltage and a grid load of 20 kV. In this case the distribution transformer load is 20 kV. Based on the simulation results with different levels of solar irradiation the voltage obtained is 19,473 V, then the expected voltage to generate a three-phase AC load that is the distribution load of the 20 kV transformer is reached. Simulation models are proposed in Matlab / Simulink 2016a Keywords: Solar Cells, Maximum Power Point Tracking, DC-DC Boost Converter, Grid